Locus of Control and Leader–Member Exchange: A Dimensional, Contextualized, and Prospective Analysis - Robert, Véronique; Vandenberghe, Christian (Frontiers in Psychology, 2020)
Since the relationship between leaders and subordinates has important implications for organizations, exploring how high-quality leader–member exchange (LMX) relationships develop over time is a critical research objective. However, LMX research has essentially focused on leader-centric approaches to describe how leaders develop differential relationships with subordinates and has devoted little attention to the influence of subordinate characteristics. This study contends that subordinates’ individual differences may act as drivers of LMX relationships. Specifically, we posited that individuals with an internal work locus of control, owing to their sense of control over the work environment, are more prone to develop high LMX relationships over time. Moreover, we expected this effect to be enhanced when these individuals are given clear expectations about their work role because such conditions would ease their sense of agency. Further, we suggested that these effects may partly depend on the dimension of LMX (i.e., affect, loyalty, contribution, and professional respect) under consideration. We argued that the effect of internal work locus of control would generalize to all LMX dimensions but that its interaction with role clarity would primarily impact the loyalty and contribution dimensions of LMX as their behavioral orientation would result in valued outcomes for internals. Data were collected through questionnaires among a sample of 424 employees working in various industries. Through a two-wave study and controlling for the autoregressive effects of LMX, subordinates’ internal work locus of control was found to enhance LMX relationships over time. Using a multidimensional approach to LMX, our results further show that the effect of internal work locus of control generalized to all dimensions of LMX. Using a contextualized view of the development of LMX, we also found that role clarity moderated the positive relationship between internal work locus of control and LMX over time such that the relationship was stronger when role clarity was high. However, from a dimensional perspective, role clarity only accentuated the relationship between work locus of control and LMX’s loyalty dimension. The implications of these findings for LMX research are discussed.